Analisis Manajemen Lalu Lintas terhadap Perubahan Arus Lalu Lintas pada Jalan Jawa dan Jalan Irian Barat - Vahlevi, Muhammad Adjie; Mahda Rkt, Nuril (Portal: Jurnal Teknik Sipil, 2025)
Traffic management is an important aspect of transportation management to overcome congestion and increase travel efficiency. The city of Medan, as one of the metropolitan cities in Indonesia, is facing big challenges due to the rapid growth of vehicles. This research aims to analyze the effectiveness of traffic management in changing the direction of flow on Jalan Java and Jalan Irian Barat, as well as identifying its impact on traffic conditions and society. This research uses a quantitative approach with survey methods, field observations, and data analysis based on Road Capacity Guidelines Indonesia (PKJI). Traffic data was collected during the three survey days before and after changes in traffic, including vehicle volume, average speed, and level of road service. From the results of the research above, it can be concluded that Javanese roads have the highest degree of saturation at 0.29 with Service Level category B means the flow is stable, but the operating speed is starting to be limited by traffic conditions. Meanwhile, the West Irian Road section has the highest degree of saturation value at 0.72 with Service Level category C in the sense that the flow is stable, but vehicle movement speed is controlled. The success of changing the direction of traffic flow is supported by infrastructure adjustments, inter-agency coordination, and active community participation. This research also recommends accelerating the underpass project on Jalan Java to support long-term mobility. It is hoped that these findings can become a reference for policy makers in implementing more effective traffic management strategies in the future.